2015
DOI: 10.1590/s0102-8650201500700000010
|View full text |Cite
|
Sign up to set email alerts
|

Photographs for anthropometric measurements of the breast region. Are there limitations?

Abstract: PURPOSE:To determine the limitations of the photographs used to obtain the anthropometric measurements of the breast region. METHODS:Five women, between the ages of 18 to 60 years, were evaluated. Photographs of the frontal and left and right profile views of their breasts were taken. Based on the current literature, the most commonly used anthropometric and anatomic landmarks for breast measurement were marked in their different positions. The different points were used to evaluate if the direct anthropometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Quieregatto et al 9 described anthropometric and anatomical points to be used for measurements using breast photography. These points were selected to standardize the measurement of breasts and to increase the reproducibility of the methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quieregatto et al 9 described anthropometric and anatomical points to be used for measurements using breast photography. These points were selected to standardize the measurement of breasts and to increase the reproducibility of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…The points analyzed were based on breast evaluations as a reference to beauty, breast symmetry, and the ideal point of the mammary papilla. Quieregatto et al, based on these studies, defined the points and the best position (frontal) that would allow study of the breasts through photographs 6,8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quieregatto et al 21 described anthropometric and anatomical points to be used for breast measurement in the frontal plane. These points were selected in order to standardize breast measurement and increase methodological reproducibility.…”
Section: Description Of the Absolute Differences Between Software Andmentioning
confidence: 99%
“…These points were selected in order to standardize breast measurement and increase methodological reproducibility. It has been shown that there are limitations on points that could possibly be used for photographic measurement in the oblique and profile views 21 .…”
Section: Description Of the Absolute Differences Between Software Andmentioning
confidence: 99%